Revitalizing Cultural Heritage: Museums’ Dynamic Role in Raising Awareness in Pakistan - Ali Raza; Abdul Wajid Moroojo; Ahsan Ul Haque Shaikh; Nurullah Pergen; Muhammad Saeed (Journal of Tourismology)
The purpose of this research was to examine how museums in Pakistan are contributing to the preservation of cultural artefacts. The purpose of this research is to identify possible ties between cultural institutions, museums, and the tourism sector that can raise consciousness among tourists. A random sampling procedure was used to select 300 participants. Data were collected from the Sindh province in Pakistan. We used qualitative data to collect information from museum curators, administrators, asset managers, and visitors. This qualitative study combined in-depth interviews with semi-structured open-ended questionnaires. There were two stages of data collection: the first involved interviews and the second involved identifying historic sites. It was determined that a proper awareness system was required; however, no culturally acceptable funding could be provided. It is easier to create a compelling presentation when there is a clearly defined national policy on cultural heritage.